Effects of ZnO/water nanofluid on the thermal performance of wet cooling towers. (November 2021) - Rahmati, Mehdi
Highlights: Investigation of ZnO/water nanofluid effect on the performance of a wet cooling tower. Improving the thermal performance of the wet cooling tower using ZnO/water nanofluid. Increasing the thermal performance of the wet cooling tower by enhancing nanofluid concentration. Employing three PVC packing with different densities. Enhancing the thermal performance of the wet cooling tower using denser packing. Abstract: This article deals with an experimental investigation on the thermal performance of a mechanical draft wet cooling tower when using Zinc Oxide (ZnO) nanoparticles and three packing types with different densities. Stable nanofluids with different weight concentrations of ZnO/water were prepared through a two-step procedure using distilled water. First of all, the influence of three packing types including 7, 9 and 18 layers are investigated on the thermal performance of the wet cooling tower using ZnO/water nanofluid with a weight concentration of 0.1%. Secondly, five ZnO/water nanofluids with weight concentrations of 0.02, 0.04, 0.06, 0.08, and 0.1% are utilized to examine the effects of nanoparticle concentration on the performance. The results indicate that water temperature difference, cooling efficiency, and tower characteristic could enhance by increasing layers of packing and weight concentrations of nanofluid. Moreover, the nanofluid effects are more notable when the denser packing is used.